2016
DOI: 10.1016/j.physbeh.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length covaries with personality in wild brown trout

Abstract: The prevalence of consistent among-individual differences in behaviour, or personality, makes adaptive sense if individuals differ in stable state variables that shift the balance between the costs and benefits of their behavioural decisions. These differences may give rise to both individual differences in, and covariance amongst, behaviours that influence an individual's exposure to risks. We here study the link between behaviour and a candidate state variable previously overlooked in the study of state-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Individuals with risky behavioural profiles (as defined above) may thus pay the costs of their fast lifestyle (increased reproductive output per breeding attempt) by reproductively senescing earlier in life. This is in line with laboratory studies showing that bold fish suffer greater oxidative stress and faster telomere attrition (Pauliny, Devlin, Johnsson, & Blomqvist, 2015), while bold fish also have shorter telomeres in the wild (Adriaenssens, Pauliny, Blomqvist, & Johnsson, 2016).…”
Section: Introductionsupporting
confidence: 89%
“…Individuals with risky behavioural profiles (as defined above) may thus pay the costs of their fast lifestyle (increased reproductive output per breeding attempt) by reproductively senescing earlier in life. This is in line with laboratory studies showing that bold fish suffer greater oxidative stress and faster telomere attrition (Pauliny, Devlin, Johnsson, & Blomqvist, 2015), while bold fish also have shorter telomeres in the wild (Adriaenssens, Pauliny, Blomqvist, & Johnsson, 2016).…”
Section: Introductionsupporting
confidence: 89%
“…Likewise, in brown trout ( Salmo trutta ), Adriaenssens et al . (using TRF) showed a relationship between telomere length and individual aggression and exploration, assuming that a shorter life span, as a result of shorter telomeres, selects for a bolder, more aggressive personality (linked to the pace of life syndrome).…”
Section: Telomeres As Biomarkers Of Aging and Correlates Of Fitness Cmentioning
confidence: 99%
“…Telomere length declined drastically during the maximal, early nestling growth period, but tail and wing length increased with relative telomere length, more so in males than females. 86 Likewise, in brown trout (Salmo trutta), Adriaenssens et al (using TRF) 87 showed a relationship between telomere length and individual aggression and exploration, assuming that a shorter life span, as a result of shorter telomeres, selects for a bolder, more aggressive personality (linked to the pace of life syndrome).…”
Section: Telomeres As Biomarkers Of Aging and Correlates Of Fitness Cmentioning
confidence: 99%
“… reference species tissue(s) method (telomere; telomerase if applicable) telomere response and effect telomerase? Adriaenssens et al [ 26 ] wild juvenile brown trout ( Salmo trutta ) fin and muscle TRF individuals with shorter fin telomeres to behave consistently more boldly and aggressively under controlled conditions in the laboratory. No such relationship was found with muscle telomere length 3–4 months after the behavioural assays n.a.…”
Section: Introductionmentioning
confidence: 99%